2020
DOI: 10.1186/s12905-020-0888-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiological indicators of the subjectively experienced health status - findings from the Women 40+ Healthy Aging Study

Abstract: Background Healthy aging is particularly important in women, as their life-span is generally longer than men’s, leaving women at higher risk for age-related diseases. Understanding determinants of women’s healthy aging is therefore a major public health interest. Clinical utility of previous research is limited, through its focus on either single psychosocial or biological predictors. The present study investigated psychobiological predictors of women’s healthy aging, for the first time includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
5
0
1
Order By: Relevance
“…Women aged 40-75 years were recruited in the context of the Women 40+ Healthy Aging Study, a larger cross-sectional investigation including healthy middle-aged and older women [72][73][74]. To be included in the study, women had to report good, very good, or excellent health.…”
Section: Subjectsmentioning
confidence: 99%
“…Women aged 40-75 years were recruited in the context of the Women 40+ Healthy Aging Study, a larger cross-sectional investigation including healthy middle-aged and older women [72][73][74]. To be included in the study, women had to report good, very good, or excellent health.…”
Section: Subjectsmentioning
confidence: 99%
“…Healthy aging is particularly important in women, as their lifespan is generally longer than that of men, leaving women at higher risk for age-related diseases [ 47 ]. Our findings may contribute to the understanding of processes of womens’ healthy aging and the development of interventions targeting these indicators, which could have significant relevance for public health.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited via flyers, Facebook, articles in health-related online portals, newsletters, and mailing lists. Women were included in the study if they reported to have at least good self-rated health ( 16 ) and fulfilled the defined inclusion criteria. These criteria were assessed first in an online self-screening and additionally confirmed by a trained study member in a telephone screening.…”
Section: Methodsmentioning
confidence: 99%